Updated knowledge and a proposed nomenclature for nuclear receptors with two DNA binding domains (2DBD-NRs). - Wenjie Wu; Philip T LoVerde (PLoS ONE, 2023)
Nuclear receptors (NRs) are important transcriptional modulators in metazoans. Typical NRs possess a conserved DNA binding domain (DBD) and a ligand binding domain (LBD). Since we discovered a type of novel NRs each of them has two DBDs and single LBD (2DBD-NRs) more than decade ago, there has been very few studies about 2DBD-NRs. Recently, 2DBD-NRs have been only reported in Platyhelminths and Mollusca and are thought to be specific NRs to lophotrochozoan. In this study, we searched different databases and identified 2DBD-NRs in different animals from both protostomes and deuterostomes. Phylogenetic analysis shows that at least two ancient 2DBD-NR genes were present in the urbilaterian, a common ancestor of protostomes and deuterostomes. 2DBD-NRs underwent gene duplication and loss after the split of different animal phyla, most of them in a certain animal phylum are paralogues, rather than orthologues, like in other animal phyla. Amino acid sequence analysis shows that the conserved motifs in typical NRs are also present in 2DBD-NRs and they are gene specific. From our phylogenetic analysis of 2DBD-NRs and following the rule of Nomenclature System for the Nuclear Receptors, a nomenclature for 2DBD-NRs is proposed.